Characteristics of Pasta Substituted with Modified Taro and Yellow Yam Flour - Arsyistawa, Hadana Sabila; Aini, Nur; Dwiyanti, Hidayah; Setyawati, Retno (Jurnal Mutu Pangan : Indonesian Journal of Food Quality, 2025)
Heat-moisture treatment (HMT) is a starch modification technique that alters the starch profile from type B to type C, characterized by low swelling power, low solubility, and strong texture stability, making it suitable for pasta production. In addition, HMT can modify physicochemical properties. This study was conducted to evaluate the physicochemical and sensory characteristics of pasta made with HMT-modified taro and yellow sweet potato flour, and to determine the treatment combination that produced the best overall quality. The experimental design used was a Randomized Group Design (RGD) with two factors: type of flour (T) and proportion of flour substitution (P). The physicochemical parameters analyzed included rehydration capacity, color, protein, fat, moisture, ash, and carbohydrate content, along with sensory evaluation. The results showed that the interaction of the two factors significantly affected all sensory parameters. The pasta with the best sensory characteristics was sample T1P3, with the following physicochemical properties: rehydration capacity (55.63%); color L* (18.71); a* (2.51); b* (3.35); protein content (12.99%); fat content (3.63%); moisture content (8.03%); ash content (3.64%); and carbohydrate content (71.71%). Sensory scores included flavor (3.87), texture (3.73), color (3.80), and overall acceptability (3.80).